EXPLORING CHINESE CULTURE THROUGH CHINESE CULINARY IN NICOLE MONES’ THE LAST CHINESE CHEF - AMALIA, RIZKY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Chinese culture, Dimensions of culture, Chinese culinary Food as the fuel of the body is an important thing in human’s life. However, the function of food can be seen in a broader context; it can reveal culture. This study is aimed to examine Chinese culture which is pictured through Chinese culinary in The Last Chinese Chef novel.Sociological approach to literature is used to analyze the novel. By using this approach, literary work is seen as the imitation of reality, thus it portrays culture as well. The understanding about culture and the dimensions of culture are also important to this study. The dimensions of culture that are discussed in this study are products, practices and perspective. Those three dimensions are completed each other in order to shape the culture.By applying the approach, this study finds that there are four cultural concepts that are exposed through Chinese culinary in The Last Chinese Chef. The first concept is harmony which can be applied in kitchen arrangement, food composition and flavor composition. The concept of harmony is important in Chinese culinary to balance the body and mind of the eater. The second concept is relationship. Eating together is Chinese’s way to make and strengthen their connection with others. The third concept is past time which can be seen through the cooks being traditional and the names of the food which have historical background. The last concept which is found is the concept of beauty. Chinese will not eat food that is not served beautifully.In conclusion, the practice and product of culture can be determinant in revealing the perspective behind it and it can be seen through something as mundane as food. For the next researcher, this novel still can be analyzed using psychological approach by focusing on the character’s personality.